EFISIENSI INVESTASI PADA PERUSAHAAN CONSUMER NON-CYCLICALS: DAMPAK CARBON CREDIT, KETIDAKPASTIAN LINGKUNGAN DAN KINERJA PERUSAHAAN - Anne Monika Fristy; Vika Miftahul Jannah; Ayuthia Ramadhani Herman; Stevanus Antoni.R (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This study aims to analyze the effect of carbon credit offset, environmental uncertainty, and firm performance on investment efficiency, while considering control variables such as firm size, leverage, firm age, and cash holdings. The research employed a quantitative method using data from 25 consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Multiple linear regression analysis was applied with the aid of SPSS, along with a normality test to ensure model validity. The results reveal that the three main variables significantly influence investment efficiency, both in models with and without control variables. However, the explanatory power of the model improved when control variables were included, highlighting that internal corporate factors reinforce the effects of external variables. These findings indicate that companies should not only focus on environmental policies and financial performance but also pay close attention to internal conditions in maintaining investment efficiency.